(untitled) (Alternautas, 2014)
The environmental crisis emerges like a civilizational crisis: a crisis of Western culture; of modern rationality; of the globalized world-economy. It is neither an ecological catastrophe, nor a simple imbalance in the economy. It is the dislocation of the world which results from the reification of being and the overexploitation of nature; it is the loss of existential meaning that comes from rationalistic thought in its negation of otherness.